1992
DOI: 10.1017/s0963180100000098
|View full text |Cite
|
Sign up to set email alerts
|

Facilitating Medical Ethics Case Review: What Ethics Committees Can Learn from Mediation and Facilitation Techniques

Abstract: Medical ethics committees are increasingly called on to assist doctors, patients, and families in resolving difficult ethics issues. Although committees are becoming more sophisticated in the substance of medical ethics, little attention has been given to the processes these committees use to facilitate decision-making. In 1990, the National Institute for Dispute Resolution in Washington, D.C., provided a planning grant from its Innovation Fund to the Institute of Public Law of the University of New Mexico Sch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

1994
1994
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(11 citation statements)
references
References 1 publication
0
11
0
Order By: Relevance
“…Methods of writing and communicating recommendations also appeared quite diverse. This diversity of approaches and methods has already been identified (Swenson, 1992;West and Gibson, 1992;Fletcher and Siegler, 1996, p. 123), as well as lack of formal procedures noted in other studies. For example, Kelly and collaborators found that cases are discussed according to positions expressed by members, and not following a formal sequential method (Kelly et al, 1997, pp.…”
Section: Case Analysis Methodsmentioning
confidence: 81%
See 4 more Smart Citations
“…Methods of writing and communicating recommendations also appeared quite diverse. This diversity of approaches and methods has already been identified (Swenson, 1992;West and Gibson, 1992;Fletcher and Siegler, 1996, p. 123), as well as lack of formal procedures noted in other studies. For example, Kelly and collaborators found that cases are discussed according to positions expressed by members, and not following a formal sequential method (Kelly et al, 1997, pp.…”
Section: Case Analysis Methodsmentioning
confidence: 81%
“…Furthermore, Bégin observed a similar phenomenon in Quebec's HECs ( ) ( ) (Bégin, 1995, p. 189). Many commentators of HECs have argued that the case analysis lacks rigor (West and Gibson, 1992;Bégin, 1995, p. 189;Kelly et al, 1997, p. 141;Rudd, 2002, p. 43) and, accordingly, HECs have been invited to clarify their procedures (Andereck, 1992, p. 49;Leeman et al, 1997, pp. 260-262;Aulisio, Arnold and Youngner, 2000, p. 65).…”
Section: Case Analysis Methodsmentioning
confidence: 99%
See 3 more Smart Citations